The role of latent toxoplasmosis in the aetiopathogenesis of schizophrenia--the risk factor or an indication of a contact with cat? - Yuksel, Pelin; Alpay, Nihat; Babur, Cahit; Bayar, Reha; Saribas, Suat; Karakose, Ali Riza; Aksoy, Cana; Aslan, Mustafa; Mehmetali, Seyfi; Kilic, Selcuk; Balcioglu, Ibrahim; Hamanca, Ozlem; et al. (Folia parasitologica, 2010)
We assessed IgG antibody to Toxoplasma gondii in 300 inpatients with schizophrenia (SG), 150 outpatients with anxiety and depressive disorders (PCG), and 150 healthy blood donors (HCG). Seropositivity rates were 60.7% for SG, 36.7% for PCG, and 45.3% for HCG (p<0.001). The seropositivity rate for anti-Toxoplasma IgG antibodies in SG was significantly higher that in PCG (chi2 = 23.11, OR = 2.66, p = 0.001) and HCG (chi2 = 9.52, OR = 1.86, p = 0.002). Among SG, 85% of those who reported close cat contact had IgG antibodies to T. gondii. Close cat contacts were reported by 59% of SG, 6% of PCG, and 9% of HCG (p<0.001). There was a nonsignificant positive association between toxoplasmosis and schizophrenia for people with a contact with a cat (OR = 2.221, p = 0.127, CI95 = 0.796-6.192), and significant negative association between toxoplasmosis and schizophrenia for people without contact with a cat (OR = 0.532, p = 0.009, CI95 = 0.332-0.854). Close cat contact (OR = 2.679, p<0.001), 51-65-year age group (OR = 1.703, p<0.001) and education [illiterate+primary (OR = 6.146, p<0.001) and high school (OR = 1.974, p = 0.023)] were detected as independent risk factors in multivariate logistic regression. The effect of toxoplasmosis on risk of schizophrenia disappeared in the complex model analyzed with multivariate logistic regression. In conclusion, our data suggest that the toxoplasmosis has no direct effect on the risk of schizophrenia in Turkey but is just an indication of previous contacts with a cat.
Keywords: senioři; toxoplazmóza; Cross-Sectional Studies; Cats; imunoglobulin G; Schizophrenia; Male; Retrospective Studies; Antibodies, Protozoan; Middle Aged; mužské pohlaví; studie případů a kontrol; průřezové studie; Adult; kočky; Toxoplasmosis; Immunoglobulin G; ženské pohlaví; zvířata; retrospektivní studie; Humans; protilátky protozoální; lidé středního věku; schizofrenie; rizikové faktory; dospělí; Female; Aged; Risk Factors; lidé; Case-Control Studies; Animals